Low and Moderate Intensity Exercise Decreased Body Fat and Increased Free Fatty Acid in Overweight Women - Dyaksa, Rizky Sota; Liben, Paulus; Mintarto, Edy (Folia Medica Indonesiana, 2021)
Highlight: • Aerobic exercise was reduced body fat and increased free fatty acids. • LICT and MICT decreased body fat and increased free fatty acids. Abstract: Overweight is fat imbalances can affect the health. It is one of the problems in many countries, especially Indonesia recorded an increase case in 2007 (8.8%) to 2013 (13.5%). Overweight categorized by 25-30 kg/m2 body mass index in units (Organization 2018). Figures overweight can be pressed to provide some treatments, such as aerobics sports activities. This study aimed to determine the effect of Continuous Low Intensity Training (LICT) and Moderate Intensity Continuous Training (MICT) to decrease body fat content (FM) and increase in free fatty acids (FFA) in overweight women. 18 female subjects completed the study 4X/week exercise LICT or MICT for 5 weeks. LICT and MICT performed for 30 minutes with an additional 5 minutes warm-up and 5 minutes of cooling down with LICT intensity of 60%-70% and MICT 70%-80% of maximum HR where both types of exercise using ergo cycle while measurement FM and FFA were measured before and after practice. LICT occurred decreasing in body fat and increasing in free fatty acids that significant pre and post LICT (p < 0.05). MICT occurred decreasing in body fat and increasing in free fatty acids that significant pre and post MICT (p<0.05). In the second comparison group (LICT and MICT) were decline against body fat and an increased in free fatty acids between workouts Low-Intensity Continuous Training (LICT) greater tendency than Moderate-Intensity Continuous Training (MICT) with delta FM (p = 0.120) and delta FFA (p=0.131) in which the value is >0.05. LICT and MICT was increase while body fat was decreased. The results of a comparison test occur list downward trend in body fat while in free fatty acids was increased.